2017
DOI: 10.2147/ott.s141117
|View full text |Cite
|
Sign up to set email alerts
|

DNA ploidy and S-phase fraction analysis in peritoneal carcinomatosis from ovarian cancer: correlation with clinical pathological factors and response to chemotherapy

Abstract: ObjectiveWe investigated the correlation between ploidy or S-phase fraction (SPF) and the clinical pathological characteristics of patients with peritoneal carcinomatosis from ovarian cancer. We also assessed their relation with the in vivo and in vitro response to several chemotherapeutic agents.Patients and methodsFifty-three patients with peritoneal carcinomatosis from ovarian cancer were enrolled. Frozen tumor tissue was dissociated by a detergent–trypsin method, and the resulting cell suspension was stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…In fact, this concept was utilised very early in the DNA index (DI), that is, the ratio of the actual DNA content of the target sample to the DNA content of normal diploid cells. If the ratio is outside the diploid and tetraploid stages, the sample is defined as aneuploid, 22,26 such as haploid, triploid and polyploid. Normal cells have a relatively constant DNA content, but structural and/or chromosomal abnormalities are common during cell carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this concept was utilised very early in the DNA index (DI), that is, the ratio of the actual DNA content of the target sample to the DNA content of normal diploid cells. If the ratio is outside the diploid and tetraploid stages, the sample is defined as aneuploid, 22,26 such as haploid, triploid and polyploid. Normal cells have a relatively constant DNA content, but structural and/or chromosomal abnormalities are common during cell carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of ploidy have different effects on the occurrence and development of tumors 19 . The overall prognosis of patients with polyploid tumors is poor, 20,21 and polyploid tumors are more malignant than haploid or diploid tumors 22,23 . However, analysis of the entire chromosome can be only used for the qualitative analysis of tumor specimens, and such analysis cannot provide specific values like TMB for the quantitative analysis of different specimens, but it can be good for predicting the therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found most glioblastomas to be aneuploidy. However, Carloni et al (2017) found that DNA ploidy was not related to SPF in . They found hyperdiploidy was encountered more frequently in primary carcinomas than in recurrent tumours.…”
Section: The Connotation Of Er and Pr On Dna Ploidy Spf And Cell Cycmentioning
confidence: 96%
“…The techniques are applied on gastroscopy, esophagoscopy, tumor flushing fluid, urine and a small amount of tissue, to analyze the cell cycle state and tumor cell alloploidy, one of the most important indicators for differentiating benign and malignant tumors and determining early diagnosis of tumors (83). In parallel, DNA ploidy of tumor cells is analyzed, and the detection rate of DNA ploidy of tumor cells is closely related to clinical biological behaviors such as tumor diffusion and metastasis (84). However, a study has suggested that DNA ploidy alone is nonspecific and may not be a good tool for assessing oral cancer prognosis or metastatic progression (85).…”
Section: Auxiliary Diagnosticmentioning
confidence: 99%